LITERATUR REVIEW TENTANG HAK PASIEN DALAM MENGAKSES INFORMASI MEDIS DAN REKAM MEDIS - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. ADIBA AISHA AMIRA, 2025)
Patients' rights to access medical information and medical records are a fundamental part of human rights guaranteed by various laws and regulations in Indonesia, such as Law No. 17 of 2023 concerning Health and Law No. 29 of 2004 concerning Medical Practice. These rights include the right to obtain clear, accurate, and easily understandable information about health conditions, medical procedures, risks, and access to the contents of medical records, as well as protection of patient medical data confidentiality. However, implementation in practice still faces challenges, including limited technological infrastructure, insufficient literacy among healthcare workers and patients, and issues related to data security and privacy. This literature review aims to analyse the legal framework, principles, and challenges in implementing the right to access medical information and medical records in Indonesia. The findings indicate the need for strengthened regulations, improved human resource capacity, and the development of an integrated and secure health information system to ensure that patients' rights are realised optimally and equitably across all regions of Indonesia.